Contribution of Zakat and Community Economic Welfare - Husain, Kamil (Indonesian Journal of Social Science Research, 2021)
This research aimed to discuss zakat in the context of contribution and community economic welfare in the perspective of zakat institutionalization and regulation, sources of foreign exchange, and distribution of capital and human development. The method used was the qualitative approach through academic literature to obtain the concepts that were relevant to the study of zakat and the community economic welfare. The data analysis process was based on the theory and concept of zakat and then followed by the data interpretation process later on. The research results showed that the dimensions of zakat institutionalization and regulation, sources of foreign exchange, and distribution of capital and human development had a very strong pattern and relationship with the dimension of community economic welfare and this was because these three dimensions were the important determinants of the contribution of zakat for the community economic welfare. On the other hand, the instrument of community economic welfare through the zakat mechanism needs to be continuously encouraged with the awareness of the entire community to pay zakat, increase the effectiveness of zakat management, and strengthen the zakat regulations.